Pharmacological Effect of Caffeine on Drosophila melanogaster: A Proof-of-Concept in vivo Study for Nootropic Investigation. - Asbah, A.; Ummussaadah, U.; Parenden, N.; Putri, A.S.W.; Rosa, R.A.; Rumata, N.R.; Emran, T.B.; Dhama, K.; Nainu, F. (Archives of Razi Institute, 2021)
A comprehensive investigation into drug candidates with nootropic activity using a proper and high throughput yet economical model organism is an important issue to consider. This proof-of-concept study was carried out to determine whether Drosophila melanogaster can be used as an in vivo screening platform to assess the nootropic activity of certain candidates for the treatment of neurodegenerative diseases. To test this, caffeine was used as a nootropic compound and a Drosophila mutant line lacking PGRP-LB with hyperactivation of NF-?B leading to early death with neurodegenerative phenotype was used as a model organism. Caffeine was orally administered via food to the PGRP-LB mutant of D. melanogaster at different concentrations (0.4 mM, 0.08 mM, 0.016 mM) prior to phenotypical observations of the survival and locomotor activity, as well as gene expression analysis, to assess the expression level of sod1, sod2, and cat genes. The results pointed out that the lifespan of D. melanogaster treated with 0.016 mM caffeine was dramatically increased; nonetheless, no changes were observed in the locomotor activity. Phenotypical analysis using a T-maze vial test demonstrated a good cognitive improvement in response to caffeine administration. Molecular analysis revealed that caffeine at a concentration of 0,016 mM induced the expression of the endogenous antioxidant genes sod1 and cat, but not sod2, signifying that the increased lifespan may be associated with a marked improvement in cytoplasmic antioxidant function. In general, the findings of the present study are in line with those previously observed in the mammalian model organism. Therefore, it can be concluded that D. melanogaster can be used as a model organism in preliminary investigation and screening of nootropic candidates prior to further testing in its mammalian counterparts.